Induction of labour versus expectant management for nulliparous women over 35 years of age: a multi-centre prospective, randomised controlled trial - Walker, Kate F.; Bugg, George; Macpherson, Marion; McCormick, Carol; Wildsmith, Chris; Smith, Gordon; Thornton, Jim (BioMed Central, 2012)
Background: British women are increasingly delaying childbirth. The proportion giving birth over the age of 35 rose from 12% in 1996 to 20% in 2006. Women over this age are at a higher risk of perinatal death, and antepartum stillbirth accounts for 61% of all such deaths. Women over 40 years old have a similar stillbirth risk at 39 weeks as women who are between 25 and 29 years old have at 41 weeks.